Design and Evaluation of a 27 MHz Microcontroller-Based Wireless Communication System for Disaster Mitigation - Jaya, Indra; Nawawi, Muhammad; Irma (Open Global Scientific Journal, 2024)
Background: Indonesia is a region frequently affected by natural disasters. During such events, critical infrastructure often suffers severe damage, and rebuilding it to a fully operational state requires a considerable amount of time. One of the key impacts of natural disasters is the damage to telecommunication networks, which necessitates rapid restoration efforts. Radio communication systems offer a viable solution for emergency communication during such times.Aims and Methods: This study presents the design of an early warning system simulator aimed at mitigating the impacts of disasters in vulnerable areas. The proposed system utilizes the ATmega328 microcontroller as the main data processor, an RX-2B module to receive 27 MHz radio signals transmitted by a TX circuit, and a TX-2B module to send wireless commands via 27 MHz radio frequency to the RX circuit. Additional components include a buzzer as an alarm indicator and a 16x2 LCD display to show patient room information. The objective of this research is to develop a microcontroller-based early warning system simulator for disaster-prone regions.Results: Based on the testing results, data transmission was successfully achieved at distances over 50 meters in indoor environments. In outdoor environments, reliable data communication was maintained at distances of up to 70 meters.